2011
DOI: 10.1080/01635581.2011.594207
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Body Mass Index in Asian Patients With Localized Renal Cell Carcinoma

Abstract: We investigated the prognostic value of BMI (body mass index) in Asian patients with RCC (renal cell carcinoma). We evaluated 170 Asian patients who underwent surgery for localized RCC (pathologic T1-4 tumors in the absence of nodal or distant metastases) between 1996 and 2004 at our institution. Patients were stratified by BMI: 22 or less vs. greater than 22. Overall, CSS (cancer-specific survival) and RFS (recurrence-free survival) was estimated using the Kaplan-Meier method. Multivariate analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…The preoperative BMI and albumin were well-known risk factors of prognosis in RCC from many studies. 22,23 As patients with higher BMI had significantly better prognosis in many studies, the present study showed similarly that BMI had a HR 0.76 (P = 0.015, 95% CI 0.611-0.949). Serum albumin was considered as a referring parameter of nutritional and performance status with BMI and other laboratory parameters, which were significant prognostic factors in previous RCC studies.…”
Section: Discussionsupporting
confidence: 75%
“…The preoperative BMI and albumin were well-known risk factors of prognosis in RCC from many studies. 22,23 As patients with higher BMI had significantly better prognosis in many studies, the present study showed similarly that BMI had a HR 0.76 (P = 0.015, 95% CI 0.611-0.949). Serum albumin was considered as a referring parameter of nutritional and performance status with BMI and other laboratory parameters, which were significant prognostic factors in previous RCC studies.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies have revealed an inverse linear relationship between obesity and RCC prognosis, which is called the obesity paradox, although the relationship has not been well established. [10][11][12][13] The present large multicenter study also revealed that BMI was a good prognostic factor for RFS and CSS among patients with nm-cRCC, although the prognostic value of obesity was affected by age, with high BMI being associated with improved RFS, and CSS among older patients (≥45 years) but not among young patients (<45 years old). To the best of our knowledge, this is the first study to clarify the agerelated prognostic value of BMI for RCC.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies have failed to detect any relationship between obesity and RCC prognosis, [7][8][9] whereas many others have revealed an inverse linear relationship that is called the "obesity paradox." [10][11][12][13] Meanwhile, a recent study has indicated that the association between obesity and RCC prognosis might be non-linear. 14 These findings suggest that other factor(s) might modify the association between obesity and RCC prognosis.…”
mentioning
confidence: 99%
“…Overweight and obesity is one of few established causes for RCC,4, 5 accounting for an estimated 40% of all cases in the US and 30% in Europe 6, 7. Paradoxically, patients with higher body mass index (BMI) also had a significantly better RCC prognosis than those with lower BMI in several studies 8–15. However, a possible association between obesity and RCC survival has not been yet generally accepted as causal and there has been no comprehensive systematic review of this association.…”
mentioning
confidence: 99%